Land and transitional justice in Brazil - Teló, Fabricio (International journal of transitional justice, 2021)
This article explores how Brazilian transitional justice has handled land dispossession suffered by peasants and Indigenous peoples during the dictatorship of 1964-1985. The article contextualizes the repression suffered by social movements fighting for land before and after the 1964 coup. Despite the fact that the National Truth Commission created a Working Group to investigate violence against peasants and Indigenous peoples, land dispossession was not considered a serious human rights violation. We also analyze the difficulties that peasants and Indigenous peoples have faced to access reparation programs implemented by the Brazilian state. Finally, we highlight the setbacks undertaken by the current and former federal governments (of Bolsonaro and Temer) in the field of transitional justice, which contribute to the continuation of violence and impunity in the present.